ChemInform Abstract: 1, 3‐Dipolar Cycloaddition of Unstabilized Azomethine Ylides by Lewis Base Catalysis. Issue 10 (7th March 2013) - Pandiancherri, Shveta; Ryan, Sarah J.; Lupton, David W.
Abstract The 1, 3‐dipolar cycloaddition of unstabilized azomethine ylides with electron‐poor olefins is achieved using Lewis base catalysis.